(3ShQI GdfhQs (3OQGSI abgjI Hjf GdTjNjf GdLdjdjf eMeO eJhdj GdTYQGhj hGHf JjejI (B/s - (3eMeO eJhdj GdTYQGhj(B.s; (3GHf JjejI(B.s ((3HjQhJ (B:s (3GdecJHI GdYUQjI(B.,s, 2005)
.
(3jJfGhd GdcJGH JaSjQ ShQI GdfhQ h HYV GdCMcGe GdNGUI HCjGJ ShQI GdfhQ(B.s
All age.
Keywords: (3ShQI GdfhQ (B-(3JaSjQ(B.s